GAMBARAN TINGKAT PENGETAHUAN TERHADAP PERILAKU PENGGUNAAN KOSMETIK DI JAGAKARSA JAKARTA SELATAN - Wulandari, Ainun; Teodhora, Teodhora; Windiarto, Henriko Suryo (Jurnal Inkofar, 2023)
Cosmetics are necessary in the beauty field for the beauty of the human body. Repeated use of cosmetic products every day requires safe requirements for someone to choose cosmetics because they add power, practicality of use, and the need to look attractive. Knowledge is a factor that influences health-related behavior, including behavior cosmetic use. This research aims to determine the level of knowledge of cosmetic use behavior among teenagers in the environment RW 03 Cipedak, Jagakarasa District, South Jakarta, and find out the relationship between knowledge and behavior in teenagers in RW 03 Cipedak Village Jagakarsa District, South Jakarta. This research is non-experimental, using analytical survey research methods with an approach, and sampling was carried out using purposive sampling. This research shows that teenagers from RW 03 Kelurahan Cipedak are a suitable category, with 89% against cosmetic use. And behavior is good, with 89.8% against cosmetic use. As well as the relationship between knowledge and behavior has a significant relationship with a value of p = 0.000.